Pengembangan Inovasi Pupuk Organik Cair melalui Kolaborasi Kampus-Masyarakat sebagai Upaya Peningkatan Pertanian Berkelanjutan di Desa Rumbio - Muhammad Fendrik; Windy Diana Manullang; Ainal Muhammad Dafiq; Vandri Riyan Nuari; Jessica Partricia Silalahi; Erza Murti Rahma; Prasetya Ramadani; Azka Salsabila; Haditha Rismawati; Lovena Melanie Putri Mahardesta; Meutya Latifahtul Badriyah; Rahmat Nofriadi (Unri Conference Series: Community Engagement, 2025)
Sustainable agricultural productivity improvement has become a major challenge in the modern era. This activity aims to develop liquid organic fertilizer (LOF) innovation from rice washing water through campus-community collaboration in Rumbio Village, Kampar District, Kampar Regency. The implementation methods include planning stage with coordination among student teams, lecturers, and village officials; socialization to farmer groups and housewives; preparation of tools and materials (rice washing water, brown sugar, EM4, and equipment); and direct demonstration of LOF production using fermentation techniques. The activity was attended by 40 participants consisting of farmer groups, housewives, and village officials. Evaluation results showed an increase in participants' understanding of organic waste utilization into LOF, with 80% of participants able to practice LOF production independently. LOF application on experimental plants showed enhanced vegetative growth compared to controls without LOF. This activity successfully improved community skills in producing environmentally friendly agricultural inputs and reducing dependence on chemical fertilizers, thus supporting sustainable agriculture.